2020
DOI: 10.1523/jneurosci.2181-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Activity Dependent and Independent Determinants of Synaptic Size Diversity

Abstract: The extraordinary diversity of excitatory synapse sizes is commonly attributed to activity-dependent processes that drive synaptic growth and diminution. Recent studies also point to activity-independent size fluctuations, possibly driven by innate synaptic molecule dynamics, as important generators of size diversity. To examine the contributions of activity-dependent and independent processes to excitatory synapse size diversity, we studied glutamatergic synapse size dynamics and diversification in cultured r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
96
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(118 citation statements)
references
References 101 publications
20
96
2
Order By: Relevance
“…Furthermore, head sizes varied more strongly not only at any given time point but also their changes over time were more variable compared to WT mice. The head size increase we observed could well represent homeostatic scaling to counteract for the loss of synaptic input 46 as a recent study demonstrated an increase in synaptic size and a broader distribution of the same in silenced neuronal networks 22 . The enhanced dynamics of spine head sizes in SOD tg mice moreover argue for a higher level of synaptic remodelling, hence synaptic instability.…”
Section: Ultrastructural Alterations Of Dendritic Spines In Sod Transsupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, head sizes varied more strongly not only at any given time point but also their changes over time were more variable compared to WT mice. The head size increase we observed could well represent homeostatic scaling to counteract for the loss of synaptic input 46 as a recent study demonstrated an increase in synaptic size and a broader distribution of the same in silenced neuronal networks 22 . The enhanced dynamics of spine head sizes in SOD tg mice moreover argue for a higher level of synaptic remodelling, hence synaptic instability.…”
Section: Ultrastructural Alterations Of Dendritic Spines In Sod Transsupporting
confidence: 65%
“…The dynamics of spine synapses, however, is only partially driven by neuronal impulse activity and synaptic transmission 10,22 . Learning-associated changes typically seem immersed in a background of spontaneous ongoing change.…”
Section: Introductionmentioning
confidence: 99%
“…This trait has also been described in the rat neocortex 28,29 . This type of distribution is characterized by a skewed curve with a long tail to the right, and it has been found in other synaptic parameters such as synaptic strength, spike transmission probability, and the size of unitary excitatory postsynaptic potentials [30][31][32][33] . It is thus tempting to suggest that the size of the synaptic junction is correlated with these and other functional characteristics of the synapse, as has been proposed previously 29 .…”
Section: Synaptic Sizes and Densities In The Hippocampus Regarding Tmentioning
confidence: 79%
“…Although the extraordinary diversity of excitatory synapse sizes is commonly attributed to activity-dependent processes that drive synaptic growth and diminution, recent studies also point to activity-independent size fluctuations, possibly driven by innate synaptic molecule dynamics, as important generators of size diversity. Specifically, activity-dependent processes seem to primarily dictate the scale rather than the shape of synaptic size distributions ( Hazan and Ziv, 2020 ).…”
Section: Discussionmentioning
confidence: 99%